Combination of Palonosetron, Aprepitant, and Dexamethasone Effectively Controls Chemotherapy-induced Nausea and Vomiting in Patients Treated with Concomitant Temozolomide and Radiotherapy: Results of a Prospective Study - MATSUDA, Masahide (Neurol Med Chir (Tokyo), 2016)
Concomitant use of temozolomide (TMZ) and radiotherapy, which is the standard therapy for patients with high-grade glioma, involves a unique regimen with multiple-day, long-term administration. In a previous study, we showed not only higher incidence rates of chemotherapy-induced nausea and vomiting (CINV) during the overall study period, but also substantially higher incidence rates of moderate/severe nausea and particularly severe appetite suppression during the late phase of the treatment. Here, we prospectively evaluated the efficacy of a combination of palonosetron, aprepitant, and dexamethasone for CINV in patients treated with concomitant TMZ and radiotherapy. Twenty-one consecutive patients with newly diagnosed high-grade glioma were enrolled. CINV was recorded using a daily diary and included nausea assessment, emetic episodes, degree of appetite suppression, and use of antiemetic medication. The percentage of patients with a complete response in the overall period was 76.2%. The percentages of patients with no moderate/severe nausea were 90.5, 100, and 90.5% in the early phase, late phase, and overall period, respectively. Severe appetite suppression throughout the overall period completely disappeared. The combination of palonosetron, aprepitant, and dexamethasone was highly effective and well tolerated in patients treated with concomitant TMZ and radiotherapy. This combination of antiemetic therapy focused on delayed as well as acute CINV and may have the potential to overcome CINV associated with a multiple-day, long-term chemotherapy regimen.